An unusual case of lung abscess secondary to round pneumonia caused by recurrent Klebsiella pneumoniae strain and the role of occult metastases tumor. (2018) - An, Shuchang; Li, Xiangli; Wei, Shenhai; Luo, Chaofeng; Cui, Rong
Abstract: Round pneumonia is an uncommon form of community-acquired pneumonia usually found in children. To this date, there has been no report on local pulmonary complications in this entity in adult patients. The present study reports a case of a 77-year-old male with lung abscess secondary to round pneumonia caused by recurrent Klebsiella pneumoniae infection accompanied by occult metastases tumor. Occult metastases may have played an important role in leading to cavity as in this present case. Further investigation regarding the relationship between recurrent infection and metastases is needed.